1999
DOI: 10.3758/bf03199729
|View full text |Cite
|
Sign up to set email alerts
|

Recognition of moving video images of conspecifics by pigeons: Effects of individuals, static and dynamic motion cues, and movement

Abstract: Two groups of pigeons were trained with a go/no-go proeedure to diseriminate video Images of eonspecifies based on the individuals or else on their aetions. Both groups showed rapid aequisition, and the diserimination transferred to new seenes in Experiment 1 and to static seenes in Experiment 2, In Experiment 3, experimentally naive pigeons were trained to diseriminate video Images of particular birds showing different aetions. Transfer to novel seenes, including a new bird and a new motion, revealed the domi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
34
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 46 publications
2
34
1
Order By: Relevance
“…They found that coherent videos supported better discrimination than did randomized one. We had thought a similar effect might occur here, but clearly did not (see Jitsumori et al, 1999 for a similar result involving forward and backward videos). Such results indicate that the motion within the video's content was not critical to the pigeons.…”
Section: Discussionsupporting
confidence: 57%
“…They found that coherent videos supported better discrimination than did randomized one. We had thought a similar effect might occur here, but clearly did not (see Jitsumori et al, 1999 for a similar result involving forward and backward videos). Such results indicate that the motion within the video's content was not critical to the pigeons.…”
Section: Discussionsupporting
confidence: 57%
“…Because the postures of a demonstrator who is pecking will differ from those of a demonstrator who is walking, it is impossible to know whether the discrimination was based on static or dynamic cues. Results described by Jitsumori, Natori, and Okuyama (1999) lend support to the first of these possibilities. The design of one of the reported experiments was similar to that used by Dittrich et al, except that the video clips were of demonstrators engaged in either key pecking or turning in circles.…”
supporting
confidence: 63%
“…More recently, pigeons have been found to categorize different video images of conspecifics based on their actions, such as pecking, circling, pacing, and walking (e.g., Dittrich et al, 1998;Jitsumori et al, 1999). Goto and Lea (2003) found that pigeons can ଝ This research was supported by Grant 13610076 from the Ministry of Education, Science, and Culture to M.J. We thank Tomoyuki Oya and Tomoya Sudo for assistance in conducting the research and Mitsuo Hanada for programming the motion stimuli.…”
Section: Introductionmentioning
confidence: 98%